FUNGSI PENCATATAN PERKAWINAN DIKAITKAN DENGAN UPAYA PERLINDUNGAN HUKUM TERHADAP ANAK SETELAH PUTUSAN MAHKAMAH KONSTITUSI NOMOR: 46/PUU-VIII/2010 - Rahmi, Atikah; Sakdul, Sakdul (Universitas Muhammadiyah Sumatera Utara, 2016)
Registration of marriage is very important for the parties in the household, as a requirement for recognition or non-recognition of marriage by the state. Registration of marriages provides authentic evidence against a persons legal status through marriage publication book or marriage certificate. Marriages that are not listed will lead the legal status of the parties to the marriage are not clear. Pursuant to Article 43 of Law No. 1 in 1974, the children born of the marriage were not recorded, did not receive judicial protection. Constitutional Court Decision No. 46/PUU-VIII/2010 implicates on changing values in society regarding the status and rights of children outside of marriage. The Constitutional Court makes decision as two sides of a coin. On the one hand protect the rights of children outside of mating, but on the other hand the decision may weaken impressed marriage function and can lead to the institution of marriage becomes less are not sacred.